Anti-SOX1 antibodies-positive paraneoplastic neurological syndromes caused by thyroid carcinoma: A case report. Issue 16 (21st April 2023) - Deng, Yazhi; Zhang, Xiaobo; Wang, Lei; Lu, Xuelin; Gao, Yunchun; Wu, Zhenkai; Zhong, Zhenzhen
Abstract : Rationale: Paraneoplastic neurological syndromes (PNSs) are a group of neurological diseases caused by distant immune effects of malignant tumors, which often occur in patients with small cell lung cancer but are not prone to occur in patients with thyroid cancer. Anti-Sry-like high mobility group box (SOX)1 antibodies (abs)-associated PNSs caused by thyroid cancer are clinically rarer. Patient concerns: A 57-year-old Chinese male patient presented with autonomic neuropathy. A thyroid biopsy revealed the diagnosis of papillary thyroid microcarcinoma. The serum anti-SOX1 abs confirmed positive. Diagnoses: A diagnosis of anti-SOX1 antibodies-positive PNS was made. Interventions: The patient received total thyroidectomy. Outcomes: After total thyroidectomy, the patient's symptoms resolved quickly, and the serum anti-SOX1 abs test results was negative on re-examination. Lessons: Thyroid cancer can cause anti-SOX1 abs-associated PNS with only autonomic neuropathy.